An analysis on user satisfaction upon using human resource information system among HR practitioners in banking sector : A case study in Bank Simpanan Nasional - Sugenesyini Nyanasegran, 1995-, author; Azlineer Sarip, supervisor; Fakulti Sains Sosial & Kemanusiaan. Sekolah Pembangunan Sumber Manusia & Psikologi (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2019